Baseline Characteristics of Fall from Height Victims Presenting to Emergency Department; a Brief Report - Hatamabadi, Hamidreza; Arhami Dolatabadi, Ali; Atighinasab, Batoul; Safari, Saeed (Archives of Academic Emergency Medicine, 2017)
Introduction: Trauma due to accidents or fall from height is a major cause of disability and mortality. The present study was designed aiming to evaluate the baseline characteristics of fall from height victims presenting to emergency department (ED). Methods: This prospective cross-sectional study evaluates the baseline characteristics of fall from height cases presenting to EDs of three educational Hospitals, Tehran, Iran, during one year. Data were analyzed using SPSS 21 and presented using descriptive statistics. Results: 460 patients with the mean age of 27.89 ± 20.95 years were evaluated (76.5% male). 191 (41.5%) falls occurred when working, 27 (5.9%) during play, and 242 (52.6%) in other times. Among construction workers, 166 (81.4%) had not used any safety equipment. Fracture and dislocation with 180 (39.1%) cases and soft tissue injury with 166 (36.1%) were the most common injuries inflicted. Mean height of falling was 3.41 ± 0.34 (range: 0.5 – 20) meters. Finally, 8 (1.7%) of the patients died (50% intentional) and 63% were discharged from ED. A significant correlation was detected between mortality and the falls being intentional (p < 0.0001) as well as greater height of fall (p < 0.0001). Conclusion: Based on the findings, most fall from height victims in the present study were young men, single, construction workers, with less than high school diploma education level. Intentional fall and greater height of falling significantly correlated with mortality.